PRIMARY HYPERHIDROSIS: EPIDEMIOLOGY, PATHOPHYSIOLOGY, CLINICAL FEATURES AND MODERN THERAPEUTIC APPROACHES — LITERATURE REVIEW - Eshonkhodjaev O.D., Amanov B.B., Yakubov B.F., Bakhromova O.A. (International Journal of Literature and Language Studies, 2026)
Primary hyperhidrosis (PHH) is a chronic disorder characterized by focal, excessive sweating beyond physiological thermoregulatory needs. Although not life-threatening, it significantly impairs quality of life, psychological well-being, and social functioning. This review summarizes current data on epidemiology, etiopathogenesis, clinical presentation, diagnostic criteria, and contemporary therapeutic strategies, including topical, systemic, and procedural interventions.